Assessing Documentation of Procedure Prerequisites in Women Undergoing Vacuum-Assisted Vaginal Delivery (VAVD) [3I]. (May 2018) - Doulaveris, Georgios; Moni, Saila; Stone, Joanne; Frieden, Faith; Atallah, Fouad; Bernstein, Peter
Abstract : INTRODUCTION: There are specific prerequisites that need to be met prior to VAVD and documented afterwards to demonstrate standard of care was met. Our objective was to examine the presence of adequate documentation in patients undergoing VAVD. METHODS: This was a retrospective cohort analysis of patients undergoing VAVD in seven academic NY hospitals over two years derived from a quality improvement database. Singletons in cephalic presentation beyond 34 weeks of gestation were included. Data was reviewed for documentation of fetal station and position, cervical dilation, pelvic adequacy, fetal heart tracing, estimated fetal weight, empty bladder, and indication. Standard univariate analyses were performed. RESULTS: 698 VAVDs were reviewed. 654 (93.7%) patients had a successful VAVD and 44 (6.3%) had a failed VAVD. In 246 cases (35.2%) at least one component was not documented; cervical dilation was most commonly omitted (74 cases, 10.6%) and indication least commonly (12 cases, 1.7%). Failed procedures had a significantly higher percentage of missing documentation for indication (6.8% vs. 1.4%, p=0.03), number of pop-offs (22.7 vs. 6.6%, p=0.0009), fetal station (27.3% vs. 3.8%, p<0.0001) and head position (36.4 vs. 4%, p<0.0001) compared to successful VAVD. Only 50% of patients with failed VAVD had adequate documentation compared to 68.5% after successful VAVD (p=0.01). CONCLUSION: VAVD is an operative procedure with significant risks. Failed procedures that require urgent cesarean present additional risk and require accurate and complete documentation. We observed that documentation was often suboptimal, particularly in unsuccessful procedures. Consideration should be given to utilizing functionality in electronic medical records to improve documentation.